Bone metabolism parameters and their relation to cytogenetics in multiple myeloma - Krhovska, Petra; Pika, Tomas; Proskova, Jitka; Balcarkova, Jana; Zapletalova, Jana; Bacovsky, Jaroslav; Minarik, Jiri (European journal of haematology, 2022)
OBJECTIVES: Our aim was to correlate serum levels of selected markers of bone metabolism and bone marrow microenvironment to cytogenetic changes in patients with multiple myeloma (MM). METHODS: We assed cytogenetic changes in 308 patients and correlated them with the following levels of bone marrow metabolism: thymidine kinase (TK), β2-microglobulin (b-2-m), Dickkopf-1 protein (DKK-1), C-terminal telopeptide collagen-I (ICTP), N-terminal propeptide of type I procollagen (PINP), receptor for interleukin 6 (rIL-6), vascular cell adhesive molecule-1 (VCAM), soluble intercellular adhesion molecule-1, osteoprotegerin (OPG), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), syndecan-1 (SYN-1) and Fas antigen. RESULT: Individuals with delRB1 had lower levels of OPG (M = 7.39 vs. 5.46 pmol/L, p = .025) and VEGF (M = 304 vs. 196 pg/ml; p = .036). t(14;16) was associated with higher β2m levels (M = 7.59 vs. 4.13 mg/L; p = .022) and lower DKK-1 levels (M = 4465 ng/L vs. 12,593). The presence of 1q21 gain was associated with higher levels of TK (M = 100.0 vs. 11.0 IU/L, p = .026) and lower levels of PINP (M = 49.3 vs. 67.4 mg/L, p = .030). CONCLUSIONS: Our analysis has shown, some cytogenetic changes, especially delRB1, t(14;16) and 1q21gain, which affect the components of the cytokine network in multiple myeloma.
Keywords: cytogenetické vyšetření; vaskulární endoteliální růstový faktor A; nádorové mikroprostředí; Tumor Microenvironment; lidé; Bone Marrow; Multiple Myeloma; kostní dřeň; mnohočetný myelom; biologické markery; Cytogenetic Analysis; Vascular Endothelial Growth Factor A; Biomarkers; Humans